Jésus. - Sertillanges, Antonin-Dalmace, O.P., 1863-1948 (Librairie Victor Lecoffre, 1900)
La Persone de Jésus -- 1 Le Berceau de Jésus -- 31 La Vie solitaire de Jésus -- 51 La Prédication de Jésus -- 83 La Prière de Jésus -- 115 Jésus et l'Autorité juive -- 147 Jésus et ses Disciples -- 181 Jésus et la Nature -- 213